PENINGKATAN SIKAP LITERASI SAINS MAHASISWA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATA KULIAH PARASITOLOGI - Hernik Pujiastutik (Biogenesis, 2018)
ABSTRACT Parasitology is the study of living organisms as parasites in humans and their relationship as causes of disease, disorders and death. In the course of parasitology, students are faced with the problem of some diseases by parasites that are widely circulated in society, so students are required to have a broader knowledge of a disease caused by parasitic organisms. Thus, the ability of literacy attitude is needed. Literacy of science is an important ability to support the ability to explain and apply science in life. However, in fact the ability of science literacy has not been trained properly. For that done a research in improving the attitude of science literacy in students. This study aims to analyze the improvement of science literacy attitude aspect in biology education students through the application of problem based learning model (PBL) in the course of parasitology. This study is a quasi experiment with non-equivalent pretest research design and posttest control group desaign. The sample of this study consists of 36 students who take the course of parasitology. Technique of data collecting is done by using scale scale of science literacy attitude which arranged by likert scale. Data analysis used SPSS 22 program. The result showed that the N-gain class of experiment and control class were in medium category (0,56 and 0,44). It can be concluded that the learning model of Problem Based Learning can improve the science literacy aspect in biology education students who take the course of parasitology. Keywords: Parasitology, Literacy and Learning Model of PBL